Transforming Waste Cooking Oil into Aromatherapy Candles to Enhance Environmental Conservation and Support Entrepreneurship Programs in Sirahan Village - Shefa Dwijayanti Ramadani; Serafica Btari Christiyani Kusumaningrum (Universitas Nurul Jadid, 2024)
Waste cooking oil is a waste product that is often not utilized optimally by the community and can pollute the environment if not managed properly. On the other hand, students at the Ibnu Hajar Community Learning Center (PKBM) and the PKK group in Sirahan Village, Magelang Regency, need to develop their entrepreneurial skills to support local economic growth. This community service project aims to provide training to both partner groups on utilizing waste cooking oil as a primary material for making aromatherapy candles. The methods employed in this activity include education and hands-on training. The results of the community service program showed that this program had a positive impact on the partner groups, namely the students of PKBM Ibnu Hajar and the PKK group in Sirahan Village. Training participants not only learned how to produce aromatherapy candles from waste cooking oil, but also gained new skills with the potential to enhance the local economy through environmentally sustainable entrepreneurship.